Association between Plasma Sestrin2 Levels and the Presence and Severity of Coronary Artery Disease. (30th June 2020) - Kishimoto, Yoshimi; Aoyama, Masayuki; Saita, Emi; Ikegami, Yukinori; Ohmori, Reiko; Kondo, Kazuo; Momiyama, Yukihiko
Abstract : Aims . Atherosclerotic disease, such as coronary artery disease (CAD), is recognized to be associated with inflammation and oxidative stress. We investigated the association between CAD and plasma levels of sestrin2 which is one of the stress-inducible antioxidant proteins. Methods . We measured plasma sestrin2 levels in 304 patients undergoing elective coronary angiography. The severity of CAD was represented as the numbers of >50% stenotic coronary vessels and segments and the severity score. Results . CAD was found in 175 patients, of whom 73 had 1-vessel (1-VD), 59 had 2-vessel (2-VD), and 43 had 3-vessel disease (3-VD). Plasma sestrin2 levels were significantly higher in 175 patients with CAD than in 129 without CAD (median 16.4 vs. 14.2 ng/mL, P < 0.05 ). A stepwise increase in sestrin2 levels was found depending on the number of >50% stenotic coronary vessels: 14.2 in CAD(-), 15.4 in 1-VD, 17.3 in 2-VD, and 17.7 ng/mL in3-VD (P < 0.05 ). High sestrin2 level (>16.0 ng/mL) was present in 38% of patients with CAD(-), 47% of 1-VD, 66% of 2-VD, and 53% of 3-VD (P < 0.005 ). Sestrin2 levels significantly, but weakly, correlated with the number of >50% stenotic segments and the severity score (rs = 0.12 and rs = 0.13, P < 0.05 ). In the multivariate analysis, sestrin2 levels were a significant factor associated with CAD independent of atherosclerotic risk factors. The odds ratio for CAD was 1.79 (95 % CI = 1.09 ‐ 2.95 ) for high sestrin2 level of >16.0 ng/mL (P < 0.025 ). Conclusions . Plasma sestrin2 levels in patients with CAD were found to be high and to be associated with the severity of CAD. High sestrin2 levels in patients with CAD may reflect a protective response against the progression of CAD.